Analysis of Drug Logistics Management at the Pharmacy Installation of Kerang Hospital Paser and Its Relationship to Patient Satisfaction - Rio Saputra; Rahmat Bakhtiar; Blego Sedionoto (Mulawarman International Conference on Tropical Public Health, 2025)
Background :Drug logistics management is a crucial component in ensuring the quality of hospital health services. The effectiveness of drug logistics management which includes planning, procurement, storage, distribution, and control directly affects drug availability and patient satisfaction. This study aims to analyze the implementation of drug logistics management at the Pharmacy Installation of Kerang Regional General Hospital (RSUD Kerang), Paser Regency, and to determine its relationship with patient satisfaction levels. Objective : The research aims to analyze the pharmaceutical logistics management at the Pharmacy Department of Kerang Regional General Hospital, Paser Regency, and to examine its relationship with patient satisfaction Research Methods/ Implementation Methods : This research employed a mixed methods approach with a sequential explanatory design, combining qualitative and quantitative methods. Qualitative data were collected through in-depth interviews with pharmaceutical management staff, while quantitative data were obtained from questionnaires distributed to 100 patients using pharmacy services. Quantitative data were analyzed using Chi-Square and multiple logistic regression tests at a 95% confidence level. Results : The results showed that the overall implementation of drug logistics management at RSUD Kerang was in the “moderately good” category, with procurement being the highest-performing aspect. The Chi-Square test revealed that only the variables of drug procurement (p = 0.011) and drug distribution (p = 0.085) had a significant relationship with patient satisfaction, whereas planning, storage, and control did not show significant effects. Multiple logistic regression analysis identified drug procurement as the most influential factor on patient satisfaction with an Exp(B) value of 3.47, followed by drug distribution with an Exp(B) value of 2.44. Conclusion/Lesson Learned : In conclusion, effective procurement and distribution of drugs are the key determinants in improving patient satisfaction with pharmacy services. It is recommended that RSUD Kerang strengthen data-based drug planning systems, accelerate procurement and distribution processes through digitalization, and enhance the competence of pharmaceutical human resources.